Reflections on climate change challenges in family house design - Parviz Munaza; Finka Maroš (Spatium)
Climate change is increasingly influencing how residential spaces are designed and used. While much attention has been given to dense urban environments, single-family homes in suburban and rural areas remain largely absent from mainstream climate strategies, despite their significant environmental footprint. This paper introduces a conceptual framework for climate-resilient housing, built around four key strategies: adaptation, mitigation, prevention, and compensation. It takes into account not only technical performance but also the spatial, ecological and social dimensions of housing. The study applies a qualitative and interpretive research approach, combining typological building analysis, environmental performance data, and literature on sustainable planning. To explore how the framework might be implemented in practice, three European case studies are used: Vauban in Freiburg, BedZED in London, and Aspern Die Seestadt in Vienna. Each of these offers a distinct model of sustainable housing development and provides a valuable basis for comparative analysis. By connecting local housing typologies with broader environmental systems, the framework contributes to a more integrated understanding of how single-family homes can actively support climate resilience. The findings offer a foundation for developing more adaptive, resource-conscious and socially inclusive approaches to residential design.